Patient and health system related factors affecting diagnostic and treatment delays in tuberculosis: A cross-sectional study in Mysuru, South India - Veerabhadra Swamy G S; Mahesh Padukudru Anand; Mahadevaiah Neelambike Sumana; N B Ramachandra; Prashanth Chikkahonnaiah; Ranjitha Shankaregowda; Jyothi M N; Chinchana Shylaja Eshwarappa; Yogeesh D Maheshwarappa; Jayaraj B S (PLoS ONE, 2026)
Tuberculosis (TB) remains a major public health challenge in India despite extensive efforts under the National TB Elimination Programme. Delays in diagnosis and treatment initiation contribute substantially to ongoing transmission and poor clinical outcomes. This study assessed the duration and determinants of patient, health system, and total delays among TB patients in Mysuru, South India. A hospital based cross-sectional retrospective study was conducted at the Princess Krishnajammanni Tuberculosis and Chest Diseases (PKTB) Sanatorium, Mysuru, between January and June 2025. A total of 331 microbiologically confirmed TB patients were interviewed using a pretested semi-structured questionnaire. Delays were defined as patient delay (>30 days from symptom onset to first healthcare consultation), health system delay (>7 days from the first consultation to treatment initiation), and total delay (>37 days). Logistic regression analysis was used to identify factors associated with prolonged delays. The median (IQR) durations for patient, health system, and total delays were 30 (25), 12 (16), and 43 (32) days, respectively. Patient delay was independently associated with informal education (AOR: 1.95; 95% CI: 1.02–3.71) and poor TB-related knowledge (AOR: 31.40; 95% CI: 3.46–284.74). Health system delay was associated with socioeconomic vulnerability, including daily wage occupation (AOR: 6.15; 95% CI: 1.81–20.85), below-poverty-line economic status (AOR: 13.89; 95% CI: 3.38–57.17), first seeking care at private facilities (AOR: 17.28; 95% CI: 5.86–50.94), and visiting more than three healthcare facilities before diagnosis (AOR: 3.01; 95% CI: 1.23–7.32). Prolonged total delay (>37 days) was associated with informal education (AOR: 4.91; 95% CI: 1.64–14.76), being married (AOR: 4.34; 95% CI: 1.12–16.85), consulting private facilities initially (AOR: 15.80; 95% CI: 5.45–45.78), and multiple healthcare visits prior to diagnosis (AOR: 24.81; 95% CI: 10.34–59.50). Nearly two-thirds of TB patients experienced diagnostic delay. Poor awareness, socioeconomic disadvantage, and initial consultations at private facilities were the major contributors. Strengthening community awareness, improving engagement with private practitioners, and addressing socioeconomic barriers are essential to reducing delays and supporting India’s TB elimination goals.